Kualitas hidup ditinjau dari pengetahuan keluarga tentang perawatan lansia - Muhammad Nur; Hamid Mukhlis (Utan Kayu Publishing, 2020)
Families have a significant role in developing, preventing, adapting, and improving health problems found in families. Family health issues are interconnected with the problems of other family members if one family member with health problems will undoubtedly affect the implementation of the functions Family. Similarly, the elderly will affect the quality of family life as a whole will affect the quality of life of the elderly. The purpose of this study to determine the relationship of family knowledge about elderly care with the quality of life in the elderly in pekon Ambarawa East 2017. type of research using quantitative design with cross-sectional.sampel in this study as many as 48 people. The results of the study were obtained from 48 people, and it is known some respondents with poor quality of life that is as many as 24 people (50 percent) and good quality of life as many as 24 people (50 percent) .of 48 people, it is known most respondents with poor quality of life that is as much 24 people (50 percent) and good quality of life as many as 24 people (50 percent), there is a relationship of knowledge with quality of life of elderly with p-value 0,037 and OR 4,491. Based on the results of the study, it is suggested to the family to increase knowledge about health care for the elderly, and families to be more active to ask health workers about the good elderly care for the sake of the quality of life of the elderly is good.